Four-quadrant operation qr-ZCS DC/DC LUO converters - Govindasamy Krishna Kumar. (2013)
Switched DC to DC converters is a method to boost voltage from a comparatively lowered battery voltage thereby saving space instead of using multiple batteries to achieve the same thing. Classical dc to dc converters employ switched mode fixed frequency pulse width modulation. But this involves hard switching effects and thereby introducing electronic noise (EMI and RFI) and complexity. Also power circuits involving this method has high switching losses.